ANALISIS PRODUKSI USAHATANI PADI SAWAH DI DESA HANDIL SURUK KABUPATEN TANAH LAUT - RABIATUL MADJDIAH; LINA SUHERTY (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2019)
The aims was conducted to decide the effect of land area, labor, fertilizer, and seed simultaneously against for rice production of rice farming of rice fields in the villages of Handil Suruk Tanah Laut district, to decide the most dominant factor, level scale farming of rice, and constraints faced by farmers. With a sample of sixty-eight samples. The data were processed by using multiple regression analysis.Variable land area, labor, fertilizer, and seed simultaneously influence on the production, while partly within the area of land and fertilizer that much influence the production of paddy rice fields in the villages of handil suruk district tanah laut, as well as the most dominant influence is variable fertilizer. The result of the function cobb-douglas started that the results from the sum of the coefficients b or a rank value of 1,361, then the level of the scale of rice farming fields in the village of handil suruk tanah laut district experience increased or increasing return to scale. The biggest obstacle the farmer is stricken with the plague of  vermin  and water, the rest is constrained as capital, difficult to find a fertilizer, and disease.Therefore, the goverment and the agency for agricultural extension (BPP) should help the farmers in setting up fertilizer, medicine, and pesticides as well as capital to build irrigation water. Keywords: rice farming production, land, labour, manure, seed